Use of a mobile application for remote monitoring of patients with chronic heart failure in clinical practice - A. R. Rustambekova; A. M. Noruzbaeva; B. T. Kurmanbekova (Евразийский Кардиологический Журнал)
The steady growth and prevalence of chronic heart failure (CHF) leads to an increase in mortality, repeated hospitalizations and disability of the population. More than half of rehospitalizations are due to poor adherence to therapy, the impossibility of timely observation by a doctor, and inadequate patient education in the basics of self-control and self-help during and after discharge. In order to improve the quality of life of patients with CHF, reduce the frequency of readmissions and mortality, it is necessary to create programs to optimize outpatient care with the possibility of monitoring clinical indicators and timely correction of therapy, which can be done using digital technologies — mHealth. The ubiquity of mobile phones and portable gadgets is thought to make the introduction of remote monitoring software more affordable and cost effective. Thus, the purpose of the review is to collect and analyze the available literature data on the use of mobile technology programs for non-invasive remote monitoring of patients with CHF. Thus, studies investigating the impact of remote monitoring on the course of CHF have included widely varying patient cohorts using dissimilar devices with different support packages. Of course, the heterogeneity of both the sample and the methods used led to the inconsistency of the data obtained, the inability to compare and evaluate the results in full. Along with this, the inability to directly compare different methods of remote monitoring of patients with CHF determines the impossibility of choosing the most effective of them, which, in turn, dictates the need for standardization of methods according to, including the healthcare system in each individual country. Overall, mHealth applications offer a potentially cost-effective solution with continued access to symptom monitoring, encouraging patient engagement in self-care and self-monitoring, and improved outcomes over standard practice. While there is considerable evidence for the effectiveness of remote monitoring programs, many areas of uncertainty remain, and mobile phone interventions require further careful evaluation. Although the available data is insufficient to confirm the impact of mobile phone monitoring, it is clear that the potential is enormous.